FEATURES OF DENTAL DISEASE PREVENTION IN CHILDREN IN THE MODERN ERA (Intent Research Scientific Journal, 2023)
The occurrence of dental caries in children is inextricably linked to the adverse effects of cariesogenic factors. These include an unbalanced diet, high carbohydrate content in foods, poor oral hygiene, environmental violations, and preventive measures. Modern equipment, new techniques, and treatments do not protect the pediatric population from new caries outbreaks. Inadequate attention to the prevention of dental diseases, especially in recent years, has contributed to the development and worsening of the course of the disease. During the transition to market relations in the Republic of Uzbekistan, the situation of preventive care for children deteriorated significantly. We analyzed the interaction of risk factors for the development of dental caries in children in Samarkand and showed that their frequent consumption of sweets and carbonated beverages and the use of sweets between meals undoubtedly damage their teeth. Therefore, schools should actively introduce the concept of "food culture" from the dentist's point of view. In this case, it is recommended that water, vegetables, and salads be consumed as the last meal of the day.